2021
DOI: 10.3390/ma14020338
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Viscosity BisGMA Derivative for Resin Composites: Synthesis, Characterization, and Evaluation of Its Rheological Properties

Abstract: This study aimed to synthesize new bisphenol A-glycidyl methacrylate (BisGMA) derivatives, targeting a reduction in its viscosity by substituting one of its OH groups, the leading cause of its high viscosity, with a chlorine atom. Hence, this monochloro-BisGMA (mCl-BisGMA) monomer was synthesized by Appel reaction procedure, and its structure was confirmed using Fourier transform infrared spectroscopy, 1H and 13C-nuclear magnetic resonance spectroscopy, and mass spectroscopy. The viscosity of mCl-BisGMA (8.3 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Furthermore, the thinning behavior could be attributed to the disruption of intermolecular interaction between resin matrix components, which is essentially driven by hydrogen bonding and pi-pi interactions, resulting from shear rate and temperature increase [ 26 ]. Compared to TBEg0 (EgGMA-free) composite, the addition of 2.5 and 5 wt% EgGMA has resulted in a reduced η *, as reported for 1.0 rad/s in Table 2 , those are from 234.70 to 86.44 and 72.34 at 25 °C, and from 52.01 to 51.81 and 30.59 (kPa·s) at 37 °C; the recorded values of η * at 0.1 rad/s as the lowest ω terminal were about 1634, 676 and 571 at 25 C, and 395, 391 and 161 (kPa·s), for TBEg0, TBEg2.5, and TBEg5, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the thinning behavior could be attributed to the disruption of intermolecular interaction between resin matrix components, which is essentially driven by hydrogen bonding and pi-pi interactions, resulting from shear rate and temperature increase [ 26 ]. Compared to TBEg0 (EgGMA-free) composite, the addition of 2.5 and 5 wt% EgGMA has resulted in a reduced η *, as reported for 1.0 rad/s in Table 2 , those are from 234.70 to 86.44 and 72.34 at 25 °C, and from 52.01 to 51.81 and 30.59 (kPa·s) at 37 °C; the recorded values of η * at 0.1 rad/s as the lowest ω terminal were about 1634, 676 and 571 at 25 C, and 395, 391 and 161 (kPa·s), for TBEg0, TBEg2.5, and TBEg5, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Bis-GMA is a base matrix compound generally convenient for its low volumetric shrinkage after polymerization, good mechanical properties, high refractive index, low volatility, and diffusivity into tissues and excellent adhesion to enamel [127,148]. Great voluminosity, strong molecular interactions driven by H-bonding, and large molecular mass are the determinants of its particularly high viscosity [149]. Nevertheless, the raised doubts about Bis-GMA low viscosity that might negatively affect mechanical properties of materials [150] and its possible cytotoxic effects linked to BPA [151,152] have started the search for alternatives and led to the marketing of Bis-GMA resin-based materials [147,153], such as Bis-EFMA-based composites [99].…”
Section: Tablementioning
confidence: 99%
“…The chemical structure of the monomer under investigation, dCl-BisGMA, was reported elsewhere [2]. The substitution generally occurs through a catalytic Appel reaction with an S N 2 mechanism, resulting in an inverted configuration [15,22,23] (Figure 1). Al-Odayni et al [2] reported some of the monomer physicochemical properties, including viscosity and biocompatibility.…”
Section: Dcl-bisgma Propertiesmentioning
confidence: 93%
“…Then, dCl-BisGMA was incorporated within unfilled resins, and its properties, including DC, water sorption (W SP ), water solubility (W SL ), and biocompatibility were evaluated. A structural modification of BisGMA with one chlorine (termed mCl-BisGMA) was also synthesized with a viscosity value of 8.3 Pa•s at 25 • C [15]. The substantial reduction in the viscosity values of mCl-and dCl-BisGMA (about 65-and 126fold, respectively, lower than BisGMA) may indicate their potential use as alternatives for BisGMA in the dental resin matrix.…”
Section: Introductionmentioning
confidence: 99%